2009
DOI: 10.1111/j.1600-0404.1980.tb01480.x
|View full text |Cite
|
Sign up to set email alerts
|

Optic neuritis as an initial symptom in multiple sclerosis

Abstract: The present study is based on a multicenter documentation system which includes standardized information on a total of 1271 patients with multiple sclerosis (MS). In 441 (34.7 %) cases the optic nerve was involved at the first appearance of the disease, and in 212 (16.6 %) subjects optic neuritis (ON) was the sole initial sign. For all MS patients with ON at the onset of the disease the female to male ratio was 1.3, whereas it was 1.5 for the whole series. The mean age at onset was 2 years lower for patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 8 publications
2
4
0
Order By: Relevance
“…In our cohort of 303 patients recruited consecutively from an MS clinic, 34.6% of them complained of permanent visual disturbances unrelated to a recent attack. The prevalence of neuro-ophthalmologic attacks at onset, 26.4% for ON and 12.2% for ocular motor manifestation, is in accordance with previous epidemiological studies reporting frequencies from 14% to 35% for ON 5,22,23 and 13% for diplopia. 22 Compared to patients without PVCs, patients with PVCs were more likely males with a progressive onset of the disease who experienced a higher number of previous neuro-ophthalmologic attacks and were more disabled.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort of 303 patients recruited consecutively from an MS clinic, 34.6% of them complained of permanent visual disturbances unrelated to a recent attack. The prevalence of neuro-ophthalmologic attacks at onset, 26.4% for ON and 12.2% for ocular motor manifestation, is in accordance with previous epidemiological studies reporting frequencies from 14% to 35% for ON 5,22,23 and 13% for diplopia. 22 Compared to patients without PVCs, patients with PVCs were more likely males with a progressive onset of the disease who experienced a higher number of previous neuro-ophthalmologic attacks and were more disabled.…”
Section: Discussionsupporting
confidence: 91%
“…In our earlier investigation when we analysed both disability and progression index, we found a more favorable prognosis for patients with initial optic nerve disturbance (15). In agreement with Sanders et al (14) a further study revealed that this difference disappeared after a disease duration of more than 10 years (16). This example shows that the parameter used in a particular study of prognosis and the length of follow-up influences the results.…”
Section: Discussionsupporting
confidence: 87%
“…Optic neuritis (ON) represents one of the most frequent phenotypes of MS relapse and occurs as the first demyelinating event in about one out of 3 MS patients [11,12]. ON offers an elegant opportunity for studies of remyelination and neuroprotection in MS [13].…”
Section: Introductionmentioning
confidence: 99%